T.R. Sullivan journal - Sullivan, T. R. (Thomas Russell), 1799-1862.
Journal (79 pages) describing a trip (1839 June-July) to Kentucky and Ohio; also includes entries from June 1861.
Author and abolitionist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kentucky -- Description and travel; Ohio -- Description and travel; United States -- History -- Civil War, 1861-1865 -- Diaries; Abolitionists; Authors